PELATIHAN KOMUNIKASI EFEKTIF GUNA MENINGKATKAN EFIKASI DIRI DALAM BERKOMUNIKASI PADA MAHASISWA - Lystia, Maria Lystia; Valezka, Caylyn; Andini, Thalia Hajar; Kesumaningsari, Ni Putu Adelia (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Effective communication skills need to be owned by students as capital in entering the world of work. Students need to be facilitated to hone and improve their effective communication skills in order to have an impact on their courage and confidence in their abilities. Effective communication training is an alternative choice of intervention. Therefore, the purpose of this research is to assist students in increasing self-confidence, both in the learning process on campus, as well as for establishing relationships with others, as well as preparation for entering the world of work later. The design of this study was a pretest-posttest control group design. The research subjects were determined using non-random sampling techniques which were divided into two groups, the experimental and control groups. The instruments used are the Self-Efficacy in Communication Scale (SEFFICAC) and the Communication Skills Scale (CSS). The results of the analysis of the paired sample t test showed that there was a significant difference in the pre-test and post-test values. Thus, effective communication training is able to have a positive influence in increasing student self-confidence.